Magnetic field in the extreme low frequency band protects neuronal and microglia cells from oxygen-glucose deprivation - Mata, Paloma; Calovi, Stefano; Benli, Kami Pars; Iglesias, Leyre; Hernández, María Isabel; Martín, Abraham; Pérez-Samartín, Alberto; Ramos-Murguialday, Ander; Domercq, María; Ortego-Isasa, Iñaki (Frontiers in Cellular Neuroscience, 2024)
Ischemic stroke consists of rapid neural death as a consequence of brain vessel obstruction, followed by damage to the neighboring tissue known as ischemic penumbra. The cerebral tissue in the core of the lesions becomes irreversibly damaged, however, the ischemic penumbra is potentially recoverable during the initial phases after the stroke. Therefore, there is real need for emerging therapeutic strategies to reduce ischemic damage and its spread to the penumbral region. For this reason, we tested the effect of Extreme Low Frequency Electromagnetic Stimulation (ELF-EMS) on in vitro primary neuronal and microglial cultures under oxygen-glucose deprivation (OGD) conditions. ELF-EMS under basal non-OGD conditions did not induce any effect in cell survival. However, ELF-EMS significantly reduced neuronal cell death in OGD conditions and reduced ischemic induced Ca 2+ overload. Likewise, ELF-EMS modulated microglia activation and OGD-induced microglia cell death.Hence, this study suggests potential benefits in the application of ELF-EMS to limit ischemic irreversible damages under in vitro stroke conditions, encouraging in vivo preclinical validations of ELF-EMS as a potential therapeutic strategy for ischemic stroke.